MATHEMATICAL PSYCHIATRY OF FIELD PLATE LOAD TEST USING FINITE ELEMENT METHOD (Malaysian Journal of Civil Engineering, 2018)
Present investigation deals with a mathematical psychiatry of Field Plate Load Test (FPLT) using FEM (Finite Element Method) in clayey soil to evolve the effect of plate dimension on settlement and coefficient of subgrade reaction (ks). A comparison between the obtained FEM results using Mohr-Coulomb’s soil model and interpretation of prior review of literature was addressed. Outcomes revealed that the ks is strictly dependent on parameters like size of the loaded area and loading magnitude, and thus completely general and generic, and not a fundamental material property of soil that can somehow be determined rationally.